P059 What Are the Biggest Concerns About Family Planning in Female and Male Perception?. (December 2019) - Lima, Fernanda; Machado, Marta
Abstract : BACKGROUND: Inflammatory Bowel Disease (IBD) predominantly affects young and reproductive age patients. Fears that IBD itself and / or its medication may inadvertently affect the course and outcome of pregnancy are a significant concern for IBD patients. The objectives were to evaluate what are the major concerns about family planning in men and women with inflammatory bowel disease. METHODS: This prospective study was conducted by a self-completed cross-sectional online questionnaire answered by 951 female and male IBD patients over 18 years of age throughout Brazil in 2019 for 10 weeks. RESULTS: A total of 951 patients answered the questionnaire, 80% (761) of the questionnaires were usable. The respondent population was 76.34% female, of these 76.38% aged between 18 and 38 years, 57.29% were diagnosed with Crohn's disease, 38.54% ulcerative colitis and 4.17% colitis. undetermined. Regarding the male data, a total of 23.66% of the sample, 78.2% were between 18 and 38 years old; 69.67% were diagnosed with Crohn's disease, 27.96% ulcerative colitis and 2.37% indeterminate colitis. The biggest concerns about family planning identified among women were: Fear of having a risky/complicated pregnancy due to illness: 62.50%. Fear of medication causing harm to baby 58.27%. Fear of illness will harm the baby: 44.49%. Fear of passing the disease to the baby: 38.60%. Fear of not being able to take care of the baby because of the disease: 36.76%. Fear of failing to get pregnant due to illness: 36.76%. The biggest family planning concerns identified among men were: Fear of not being able to take care of the baby because of the disease: 39.42%. Fear of passing the disease to the baby: 28.85%. Other: 22.60%. Fear of illness will harm the baby: 19.71%. Fear of medication causing harm to baby 12.02%. Fear of not being able to get pregnant due to illness: 11.54%. Fear of partner having a risky/complicated pregnancy because of my illness: 7.69% CONCLUSION(S): The data show that men are less afraid than women, both care-related and drug-related, this concern is expressed even in the number of male responders, notably smaller. Among the concerns presented by both sexes, they fear that IBD could lead to a complicated pregnancy and that the disease itself could cause fetal harm or hinder the care of the baby.